The genes raw and ribbon are required for proper shape of tubular epithelial tissues in Drosophila. - Jack, J.; Myette, G. (Genetics, 1997)
The products of two genes, raw and ribbon (rib), are required for the proper morphogenesis of a variety of tissues. Malpighian tubules mutant for raw or rib are wider and shorter than normal tubules, which are only two cells in circumference when they are fully formed. The mutations alter the shape of the tubules beginning early in their formation and block cell rearrangement late in development, which normally lengthens and narrows the tubes. Mutations of both genes affect a number of other tissues as well. Both genes are required for dorsal closure and retraction of the CNS during embryonic development. In addition, rib mutations block head involution, and broaden and shorten other tubular epithelia (salivary glands, tracheae, and hindgut) in much same manner as they alter the shape of the Malpighian tubules. In tissues in which the shape of cells can be observed readily, rib mutations alter cell shape, which probably causes the change in shape of the organs that are affected. In double mutants raw enhances the phenotypes of all the tissues that are affected by rib but unaffected by raw alone, indicating that raw is also active in these tissues.